2017
DOI: 10.1155/2017/4105713
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic Intervention to Impacted and Transposed Lower Canines

Abstract: Impacted and transposed teeth cause serious difficulties in tooth eruption and movement as well as esthetic and functional outcomes. Proper treatment planning including good biomechanical control is essential in order to avoid side effects during traction and aligning of the impacted and/or transposed teeth. The purpose of the present study was to present a successfully treated female patient having transposed and impacted lower canines by means of a modified lingual arch and fixed orthodontic appliance. A fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…operative control, as well as patient awareness and collaboration are highly relevant aspects for the success or failure of treatment. In cases of failure, alternative approaches should be brought to the attention of patients, parents and caregivers [8,10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…operative control, as well as patient awareness and collaboration are highly relevant aspects for the success or failure of treatment. In cases of failure, alternative approaches should be brought to the attention of patients, parents and caregivers [8,10].…”
Section: Discussionmentioning
confidence: 99%
“…According to Bishara, et al [3], the main signs to be observed in the clinical examination are: delay of eruption after the age of 14 years, prolonged retention of primary canines, elevation of the labial or palatal mucosa, distal migration of the upper lateral incisor, with or without deviation of the medium line. Radiographic examination is essential in the radiographic elaboration, as it proves the canine impaction and its location in the vestibular-lingual, cervico-occlusal and mesio-distal directions, as well as its relation with adjacent structures [7,8].…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 Presently, there are several treatment options available to address transmigrated canines, including radiographic observation, autogenous transplantation, orthodontic treatment and tooth extraction when there is inadequate space to realign the tooth. 5 There have been incidences of complications associated with the extraction of impacted teeth like trismus, inflammation, mild to moderate pain, hematoma and bony defects. 6 Different studies have reported that some patients who have been operated on the symphysis, suffered changes in their facial contour and aesthetic changes in the symphysis zone.…”
Section: Introductionmentioning
confidence: 99%